CONSIDERATION OF AERODYNAMIC IMPACT IN SETTING THE MAXIMUM PERMISSIBLE SPEEDS OF HIGH-SPEED TRAIN - Djabbarov, S. T. (Science and Transport Progress, 2017)
Purpose. Studies of the effect of aerodynamic pressure on the maximum permissible speeds of a high-speed train on the existing railway infrastructure. Methodology. The study of the magnitude and direction of the aerodynamic pressure, its effect on the maximum speeds of a high-speed train was carried out on a train model composed of axisymmetric bodies with conical forms of head and tail parts. Findings. Determined the values of the aerodynamic pressure at different distances from the train are, when the high-speed train moves at a speed of 200 km/h or more. The maximum speeds of a high-speed train are determined taking into account the state of the infrastructure of the existing railway, ensuring the safe operation of a high-speed railway. Originality. Theoretical studies of aerodynamic pressure from secondary air currents formed during the movement of high-speed trains are performed on a model of a train composed of identical axisymmetric bodies with conical forms of head and tail moving in a compressible medium. The results of the research allow the regularity of the change in aerodynamic pressure during the movement of a high-speed train. Practical value. The obtained results allow to establish: 1) the maximum permissible speeds of a high-speed train taking into account the technical condition of permanent devices and structures of the existing railway infrastructure; 2) technical parameters of individual objects and structural elements of the infrastructure of high-speed iron subjected to the effect of aerodynamic pressure for a given maximum speed of high-speed trains.